2008
DOI: 10.1016/j.jcin.2008.07.007
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Cardiac Interventions

Abstract: The field of pediatric cardiac interventions has witnessed a dramatic increase in the number and type of procedures performed. We review the most common procedures performed in the catheter laboratory. Lesions are divided according to their physiological characteristics into left-to-right shunting lesions (atrial septal defect, patent ductus arteriosus, ventricular septal defect), right-to-left shunting lesions (pulmonary stenosis, pulmonary atresia/intact ventricular septum), right heart obstructive lesions (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 93 publications
1
22
0
1
Order By: Relevance
“…2 Coarctation is more common in male than female. 2,8 Our study also showed male preponderance. The management of patient presenting with neonatal coarctation is revolutionized by invention of prostaglandin E and its use to restore the patency of the ductus.…”
supporting
confidence: 73%
“…2 Coarctation is more common in male than female. 2,8 Our study also showed male preponderance. The management of patient presenting with neonatal coarctation is revolutionized by invention of prostaglandin E and its use to restore the patency of the ductus.…”
supporting
confidence: 73%
“…One example is a possible evolution of pulmonary hypertension, resulting from the adaptation of pulmonary flow postoperatively, a situation that restricts sudden maneuvers of physiotherapy [4,8,16,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, attention should be paid to patient positioning, which must be at least 45 degrees of elevation, and avoid an increase in pulmonary vascular resistance with maintenance of PEEP (positive end expiratory pressure) low (up to 5 cmH20) [ 4,8,16,[19][20][21].…”
Section: Discussionmentioning
confidence: 99%
“…Introduction of interventional catheterization opened new venues in the treatment of patients with congenital heart disease [1]. Before this era, very sick or neglected patients were either denied surgery or underwent high risk procedures.…”
Section: Introductionmentioning
confidence: 99%